(untitled) (Quest Journal of Management and Social Sciences, 2024)
Purpose: The present paper aims to analyse the new financial system related to cryptocurrency and its challenges. Methodology: This paper primarily employs a literature review and quantity methodology to elucidate the emerging financial paradigm, hindrances, and policy considerations. Findings: The findings indicate that cryptocurrency can transform the financial landscape. Moreover, the data reflects that the transactions of different cryptocurrencies are increasing. Conclusion: The global payment system is experiencing significant changes due to cryptocurrency and the implementation of blockchain technology. It contends with challenges like price fluctuations and security threats. Further research is needed to understand the implementation of cryptocurrency as a common currency and its effects. Keywords: Bitcoins, Cryptocurrency, Digital Economy, Blockchain technology, Peer to Peer and Bitcoin